Les sources - Drine, Ali (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie -- Djerba

The excavations: Schnitt 8 – ein heiligtum der isis? - Apatsidis, Marina; Köppe, Alexander; Ritter, Stefan; Scheding, Paul (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2017, 2022)
Keywords: Archéologie -- Djerba

Les mosaïques romaines de Meninx - Arndt, Robert C. (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The excavations: Trench 5 – a late roman domestic building - Arndt, Robert C.; Kerschbaum, Saskia (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The excavations: Trench 4 – early punic occupation and roman forum - Arndt, Robert C.; Stoeßel, Linda; Gabler, Lena; Aoudi, Mekki (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2016, 2022)
Keywords: Archéologie -- Djerba

The quarries - Beck, Dennis Mario (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

La céramique - Ben Tahar, Sami; Mansel, Karin; Mukai, Tomoo (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Liste des datations des unités stratigraphiques (SE) de Meninx 2017–2018 - Ben Tahar, Sami; Mansel, Karin; Mukai, Tomoo; Assirelli, Francesca; Mancini, Bianca (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2015, 2022)
Keywords: Archéologie -- Djerba

Appendix: The radiocarbon analyses - Dinies, Michèle; Fiederling, Max (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Crop cultivation and land-use on djerba from phoenician times to late antiquity (4th cent. B.C.–6th cent. a.D.): a synthesis of first archaeobotanical investigations - Dinies, Michèle; Podsiadlowski, Viola; Neef, Reinder (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Ceramics and other finds from the underwater archaeological investigations - Fiederling, Max (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The underwater archaeological investigations (with trenches 10–12) - Fiederling, Max; Pflederer, Tobias; Gadhoum, Ahmed (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2018, 2022)
Keywords: Archéologie -- Djerba

Ein marmorkopf des antoninus pius aus meninx - Gabler, Lena (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The coin finds - Kerschbaum, Saskia (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Fragmentierte Skulptur: ein monumentaler Kopf des Serapis vom antiken Forum - Kovacs, Martin; Lipps, Johannes (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The Excavations: Secteur 2 – Une maison punique et son occupation jusqu’à la fin de l’Antiquité - Lamare, Nicolas (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The Excavations: Secteur 9 – Des citernes publiques et un complexe industriel - Lamare, Nicolas (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The excavations: Schnitt 3 – ein thermengebäude am forum - Lehnert, Christoph; Ritter, Stefan (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Architekturhistorische untersuchungen in meninx – die bauteile im pavillon - Lipps, Johannes (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Die funde: Einführung - Mansel, Karin (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Kleinfunde aus metall, bein und stein - Ortisi, Salvatore (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Wandmalerei und bemalter Stuck aus Meninx - Ritter, Stefan; Scheding, Paul; Kranz, Sebastian (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Le terracotte architettoniche: antefisse italiche e locali dal Foro - Scheding, Paul (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Die glasfunde aus meninx - Schmittner, Stephanie (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Römische statuetten aus den thermen (schnitt 3) - Schöpflin, Bartlin (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The excavations: Trench 1 – a main road through meninx in the area of the macellum - Sheldrick, Nichole (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The excavations: Trenches 7 and 13 – a cross-section of meninx’s urban core - Sheldrick, Nichole (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The excavations: Schnitt 6 – die forumsbasilika - Stoeßel, Linda (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Ton-model in form eines equiden - Thois, Julia (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Archaezoology in meninx: Palaeoeconomy between local economic structure and supra-regional network - Trixl, Simon; Peters, Joris (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Fish exploitation at meninx - Van Neer, Wim; Wouters, Wim; Trixl, Simon (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Der nördliche zisternenkomplex – bauforscherische untersuchung der freiliegenden strukturen - Wolf, Kilian (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The Urban History of Meninx: A Synthesis of our Results - Ritter, Stefan; Ben Tahar, Sami (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The Urban Layout: Results of the Magnetometer Survey - Fassbinder, Jörg W. E.; Ritter, Stefan (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

The Database Management - Scheding, Paul; Watson, Juliane (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Archaeological Geophysics - Fassbinder, Jörg W. E. (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Engineering Geodesy in Meninx - Weinhuber, Agnes (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Introduction: The History of Research on Meninx and our Objectives - Ritter, Stefan; Ben Tahar, Sami (Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019, 2022)
Keywords: Archéologie -- Djerba

Des pots dans les voûtes et la datation des mosquées de Djerba - Fentress, Elizabeth (La production et la circulation de la céramique en Afrique du Nord de l'Antiquité tardive à la période postmédiévale (VIe-XVIIIe siècle), 2025)
Keywords: Archéologie -- Djerba; Céramique -- Djerba

Fin de la campagne de nettoyage sur le site archéologique Henchir Bourgou (Djerba) (DARTCreations, 2025)
L’Association pour la sauvegarde de l’île de Djerba (Assidje), sous la supervision de l’Institut national du patrimoine (INP), a achevé une vaste campagne de nettoyage sur le site archéologique Henchir Bourgou. Les interventions ont porté notamment sur l’évacuation des gravats et des déchets de matériaux de construction, ainsi que sur la sécurisation du lieu grâce à l’installation d’un talus de terre agrémenté de figuiers de barbarie, typiques du paysage djerbien.Ces travaux ont permis de redonner au site une nouvelle allure, tout en le protégeant d’éventuelles atteintes à son intégrité patrimoniale, dans une démarche globale de préservation et de valorisation. Situé au nord de la route reliant Houmt Souk à Midoun, ce site, classé monument historique depuis 2022, abrite un mausolée dont la construction remonte à la première moitié du IIème siècle avant J.-C. Il constitue l’un des témoignages archéologiques les plus remarquables de l’architecture funéraire numide et punique de la période hellénistique. Selon les données recueillies par l’Assidje, ce mausolée aurait appartenu à un fortuné notable, allié du célèbre souverain numide Massinissa.A travers cette initiative, l’Association pour la sauvegarde de l’Ile de Djerba poursuit sa démarche visant à inscrire Henchir Bourgou dans un processus durable de valorisation. Une seconde étape est déjà envisagée, afin d’intégrer le site au parcours touristique et culturel de l’île, pour renforcer davantage son rayonnement patrimonial. Il est à noter que, dans le cadre de ses activités scientifiques, l’Institut national du patrimoine a mené en juin et juillet 2023 une fouille au cœur de l’ancienne agglomération antique de Henchir Bourgou. Cette campagne a révélé les vestiges d’une vaste demeure construite à l’époque augustéenne, remaniée durant la période flavienne, puis abandonnée à la fin du IIème siècle ou au début du IIIème siècle après J.-C. Ces découvertes confirment l’importance historique et archéologique de cette cité antique à Djerba. Ses sols en opus signinum de tradition punique témoignent à la fois de la richesse du propriétaire de cette demeure et de la persistance de la culture héritée de Carthage en pleine époque romaine, selon des informations publiées par l’INP.
Keywords: Archéologie -- Djerba

Les artefacts de Meninx - Drine, Ali (6e colloque international: La Circulation des Hommes, des Objets et des Idées en Méditerranée Antique et Médiévale, 2025)
Keywords: Archéologie -- Djerba

L’occupation préhistorique en milieux insulaire et continental : le cas des îles de Djerba, Kerkennah et de la presqu'île de Zarzis - Hannachi, Khansa (جزيرة جربة عبر التاريخ: من المحليّة إلى العالميّة | L'île de Djerba à travers l'histoire : Du local au mondial, 2025)
"Une prospection pédestre menée sur l’île de Djerba a révélé une occupation humaine remontant à la Préhistoire. Les traces mises en évidence comprennent du matériel lithique limité, provenant de cinq stations. Cette rareté pourrait s’expliquer par plusieurs facteurs, notamment l’utilisation de matériaux périssables pour la fabrication d’outils, ou encore l’abondance de mollusques, qui auraient pu constituer une ressource utilitaire privilégiée pour les communautés humaines de l’époque. En comparaison, les découvertes lithiques réalisées sur l’île de Kerkennah sont significativement plus abondantes, suggérant des différences dans les modalités d’occupation. Sur Djerba, la faible densité de matériel semble indiquer des occupations saisonnières, probablement influencées par des conditions environnementales spécifiques, telles que des difficultés d’accès ou des contraintes climatiques. Les données archéologiques recueillies sur Djerba permettent toutefois de situer ces occupations préhistoriques entre le Paléolithique moyen et l’Épipaléolithique. Une comparaison avec la presqu’île de Zarzis met en lumière des différences notables. Contrairement à Djerba, Zarzis présente une densité importante de sites archéologiques, répartis autour des sebkhas et le long des côtes sableuses. Ces découvertes témoignent d’installations plus permanentes, probablement rendues possibles par des conditions environnementales plus favorables, telles qu’une diversité accrue de ressources naturelles. Cette disparité entre les deux régions reflète les contrastes marqués entre un milieu insulaire, propice à des occupations temporaires et opportunistes, et un milieu continental, offrant des conditions plus stables et propices à l’établissement de communautés humaines sur le long terme."
Keywords: Archéologie -- Djerba

‘How were the traces of their edifices erased?’ Archaeological / ethno-historical survey of Jerba, Tunisia - Holod, Renata (Khalili Research Centre Seminars, 2017)
Keywords: Archéologie -- Djerba

Novità nello scriptorium dei Romani - Pappalardo, Umberto (Minima epigraphica et papyrologica, 2021)
Purchase online the PDF of Novità nello scriptorium dei Romani, Pappalardo, Umberto, 1949- -
Keywords: Archéologie -- Djerba

Ritter Stefan, Ben Tahar Sami (éd.), Studies on the Urban History of Meninx (Djerba). The Meninx Archaeological Project, 2015–2019 (Archäologische Forschungen, 43), Wiesbaden, DAI-Reichert, 2022, 1 vol. 21 × 30, Volume I, 454 p. + 11 pl., 248 fig. n/b et coul., ISBN : 978-3-75200-611-7. - Bejaoui, Fathi (Revue archéologique, 2024)
Keywords: Archéologie -- Djerba; Recension

Sami Ben Tahar, Activités: Site de Henchir Bourgou (Jerba) - Dabbaghi, Ali (Institut national du patrimoine, 2023)
Sami Ben Tahar, Chercheur archéologue à l'INP Site de Henchir Bourgou (Jerba), une fouille extensive Dans le cadre des activités scientifiques de l’INP une fouille extensive a été menée sur le site de Henchir Bourgou (Jerba) au cœur de l’agglomération urbaine antique au courant des mois de juin et juillet 2023. Elle a livré des une fouille extensive a été menée sur le site de Henchir Bourgou (Jerba) au cœur de l’agglomération urbaine antique au courant des mois de juin et juillet 2023. Elle a livré des vestiges afférents à une grande maison construite à l’époque augustéenne, réaménagée à l’époque flavienne et complètement abandonnée vers la fin du IIe s. ou au tout début du IIIe s. ap. J.-C.
Keywords: Archéologie -- Djerba

statue [homme (drapé)]
homme (drapé) ; ; Etat de l'oeuvre : il reste la partie inférieure de la statue, du nombril aux chevilles.
Keywords: Archéologie -- Djerba

statue [magistrat]
magistrat (?, toge, calceus) ; support (volumen, plusieurs) ; ; Etat de l'oeuvre : incomplet-moins le haut du buste,main gauche,main droite tenant la toge-éclats(plis de la toge en haut du buste et au dessus de l'abdomen)
Keywords: Archéologie -- Djerba

Tsunami deposits in Tunisia contemporaneous of the large 365 CE Crete earthquake and Mediterranean Sea catastrophic event - Bahrouni, Nejib; Meghraoui, Mustapha; Bayraktar, Hafize Başak; Lorito, Stefano; Zagrarni, Mohamed Fawzi; Polonia, Alina; Bel Mabrouk, Nabil; Kamoun, Fekri (Scientific Reports, 2024)
New field investigations along the East Tunisian coastline reveal sedimentary deposits and damaged localities that may account for a catastrophic event during the late Holocene. North of Sfax city, ~ 3.4 m high cliff coastal marine and alluvial terraces show 20 to 50-cm-thick chaotic layer with sandy coarse gravels mixed with reworked pebbles, broken shells of gastropods and molluscs, organic matter and Roman pottery. The chaotic layer truncates sandy-silty paleosol, covers Roman settlements and is overlain by fire remains, a thin sandy-silty aeolian unit and ~ 1-m-thick alluvial deposits. Charcoal samples collected at 10 cm below and 4 cm above the catastrophic deposits provide radiocarbon dating that brackets the catastrophic unit between 286 and 370 CE. Other historical investigations on the Roman sites of Neapolis (Nabeul), Hadrumete (Sousse), Thyna (Sfax), Meninx in Girba (Djerba), Wadi Ennouili (Gulf of Gabes), and Sabratha (in Libya) evidenced major damage and abandonment of sites in the fourth century (16, 41, 42, 43, 44). The new identification of catastrophic deposits, offshore-onshore correlations with turbidites and modelling of tsunami waves suggest the relationship with the 21 July 365 tsunamigenic earthquake (Mw ~ 8) of west Crete (Greece) and call for a better estimate of tsunami risk on the Mediterranean coastlines.
Keywords: Archéologie -- Djerba; Séisme -- Djerba -- 0365

Un tsunami a dévasté 800 km de côte dans cette région de la Méditerranée il y a 1 600 ans ! - Gillard, Morgane (Futura, 2024)
Les documents historiques nous révèlent que le 21 juillet de l’an 365, un puissant séisme s’est déclenché au niveau de l’île de Crète, générant un tsunami dont les vagues auraient ravagé les côtes...
Keywords: Archéologie -- Djerba

Meninx - Huß, Werner (Brill’s New Pauly, 2006)
(Μῆνιγξ; Mêninx). Island (modern Djerba) and city (modern al-Kantara) in the province of Africa Tripolitana ( Africa [3]). Eratosthenes (fr. p. 308 Berger, in Plin. HN 5,41) describes the island as ‘lotus-eating’ (λωτοφαγῖτις; lōtophagîtis). Sources: Ps.-Scyl. 110 (GGM 1,85-89); Pol. 1,39,2; 34,3,12; Str. 3,4,3; Mela 2,105; Ptol. 4,3,35; 8,14,13; Stadiasmus Maris Magni 103; 104; 112; 124 (GGM 1,465f.; 468; 471). In 253 BC the Roman fleet ran into diffilculties off M. ((Pol. 1,39,2). In 217 BC the island was laid waste by the Romans (Liv. 22,31,2). Marius [I1] landed on the island during his flight to Africa (Plut. Marius 40,4). Contrary to [Aur. Vict.] Epit. Caes. 30,1-31,1, M. was not the home of the emperors Trebonianus Gallus and Volusianus (251-253).
Keywords: Archéologie -- Djerba

المشهد الجنائزي في جزيرة جربة في العصور القديمة من خلال مثالي السوق القبلي ومرقان - بن طاهر, سامي (الحياة الثقافية, 2008)
Keywords: Archéologie -- Djerba

موقع ميننكس- هنشير القنطرة- جربة - درين, علي (الحياة الثقافية, 2008)
Keywords: Archéologie -- Djerba

Maʿālim wa mawāqiʿ Janūb Jazīrat Jarba - Drine, Ali (al-Jazira, 2001)
Keywords: Antiquité; Archéologie -- Djerba; Monuments -- Djerba

Découverte majeure à Djerba, un hypogée avec son mobilier fu-néraire intact datant du IIème s. ap. Jc. - Bouabid, Naceur (Le Temps, 2014)
Keywords: Archéologie -- Djerba

Une tombe datant du IIème siècle Après JC retrouvée à Guellela (Webdo, 2014)
Une tombe avec son mobilier funéraire, en date du IIème siècle après JC a été découverte le 11 juin dans la région de Tlat - Guellala
Keywords: Archéologie -- Djerba

Découverte majeure à Djerba : Un hypogée avec son mobilier funéraire intact datant du IIème siècle Ap.Jc - Bouabid, Naceur (Le Temps, 2014)
Des travaux ordinaires de terrassement entrepris par un propriétaire d’un terrain sis à Tlet de la circonscription de Guellala, délégation Djerba-Adjim, ont permis derévéler au grand jour une dé
Keywords: Archéologie -- Djerba

Archéologie : Les étudiants de l’Iset au chevet de Henchir Bourgou - Kapitalis - Bouabid, Naceur (Kapitalis, 2015)
Des étudiants de l’Iset Djerba volent au secours du site archéologique de Henchir Bourgou, à Djerba. Une initiative qui mérite toutes les louanges.
Keywords: Archéologie -- Djerba

Nouvelles découvertes archéologiques au site de Zian à Zarzis - Kapitalis - Bouabid, Naceur (Kapitalis, 2015)
Des archéologues tunisiens et américains ont fait de nouvelles découvertes dans ce site antique de Zian à Zarzis encore méconnu.
Keywords: Archéologie -- Djerba

Studies on the urban history of Meninx (Djerba): the Meninx archaeological project 2015-2019 - Ritter, Stefan; Ben Tahar, Sami (Archäologische Forschungen, 2022)
Dans l'Antiquité, Meninx était le chef-lieu de l'île de Djerba qui a donné son nom à l'île. Cette vaste ville portuaire, située dans un golfe protégé, était l'un des plus importants centres de production de pourpre en Méditerranée et devint l'une des plus grandes métropoles d'Afrique du Nord romaine. En 2015, un projet de recherche archéologique a été initié en coopération entre l'Institut d'archéologie classique de l'Université de Munich et l'Institut national du patrimoine, Tunisie, afin d'explorer le développement urbain de ce site antique jusqu'alors peu connu. Dans un premier temps, une prospection géophysique à grande échelle a permis de clarifier la structure du site urbain. Lors de deux campagnes de recherche sur le terrain en 2017 et 2018, des fouilles ciblées ont été menées, qui ont permis, grâce à leur riche matériel, de jeter un regard exemplaire sur différents domaines de la vie urbaine à toutes les périodes de l'histoire de l'habitat, de l'époque punique à l'Antiquité tardive (IVe siècle av. J.-C. à VIIe siècle après J.-C.). De plus, des recherches archéologiques sous-marines ont permis d'obtenir pour la première fois des informations sur les installations portuaires de Meninx. Le présent ouvrage propose une synthèse des multiples résultats de ces recherches. Il en ressort que Méninx, avec ses contacts économiques régionaux et suprarégionaux, jouait un rôle central pour l'île, qui faisait office de carrefour entre les réseaux commerciaux maritimes méditerranéens et le continent tout proche, avec ses routes commerciales menant au Sahara. Dans son rôle de centre de production et de commerce, Meninx se distinguait nettement des autres métropoles côtières tripolitaines, Sabratha et Lepcis Magna, par le fait que la vie urbaine était entièrement centrée sur la mer et ses ressources.
Keywords: Archéologie -- Djerba

Looking over the builders’ work: foreign architects, artisans, and marble at Meninx (Djerba) - Lipps, Johannes (Libyan Studies, 2022)
Throughout the second century AD, the civic centres of the wealthy coastal cities of Africa Proconsularis underwent deep-rooted changes. Up to this point local stone had been largely employed for their buildings, but from the Hadrianic period onwards there was an increasing use of marbles, which were imported with considerable efforts and at great expense. These marbles came primarily from Italy, Greece, and Asia Minor, and brought with them new architectural concepts, as well as architects and artisans who have been generally identified as ‘Italian’ and ‘Eastern’ in past scholarship. This article will examine a temple, a structure presumed to be a portico, and a basilica from the harbour city of Meninx, located in southern Djerba (Tunisia). The exceptionally good preservation of these buildings’ architectural components and the documentation produced during their on-site recording in 2017–18 allow for a detailed understanding of their original building processes. This will show how mobile the building industry of the Roman Empire was during the second century AD, which in turn challenges any attempts of an overly schematic territorial placement of architectural concepts, building traditions, and the provenance of the artisans themselves., إلقاء نظرة على أعمال البنائين : المهندسين المعماريين والحرفيين الأجانب والرخام في مننكس (جربة), يوهانس ليبس, خلال القرن الثاني الميلادي، خضعت المراكز المدنية للمدن الساحلية الغنية في أفريقيا بروكونسولاريس لتغييرات عميقة الجذور. وحتى تلك اللحظة، كان الحجر المحلي مستخدماً إلى حد كبير في مبانيها، ولكن منذ عصر هادريان وما بعده كان هناك استخدام متزايد للرخام، والذي تم استيراده بجهد وتكلفة كبيرين . جاءت هذه الكتل الرخامية بشكل أساسي من إيطاليا واليونان وآسيا الصغرى، وجلبت معها مفاهيم معمارية جديدة، بالإضافة إلى مهندسين معماريين وحرفيين تم تحديدهم في الدراسات السابقة عموماً على أنهم ”إيطاليون “ و ”شرقيون “. ستفحص هذه المقالة معبداً، ومعلم يُفترض أنه رواق، و باسيليكا من مدينة المرفأ مننكس الواقعة في جنوب جربة (تونس ). حيث سمح الحفظ الاستثنائي الجيد على المكونات المعمارية لهذه المباني والوثائق التي تم إنتاجها أثناء التوثيق في الموقع في 2017–2018 على فهم تفصيلي لعمليات البناء الأصلية. و سيوضح هذا كيف كانت صناعة البناء في الإمبراطورية الرومانية متحركة خلال القرن الثاني الميلادي، و التي بدورها تتحدى أي محاولات مفرطة لوضع اطار إقليمي تخطيطي لمفاهيم معمارية، وتقاليد بناء، و موطن الحرفيين أنفسهم .
Keywords: Archéologie -- Djerba

Adaption and Autonomy in the Architecture of Roman North Africa. The Basilica of Meninx, a Case Study - Stoeßel, Linda (The Basilica in Roman Palestine: adoption and adaption processes, in light of Comparanda in Italy and North Africa: workshop, 5-6 December 2019, Tübingen, 2021)
Keywords: Archéologie -- Djerba

Quelques remarques sur la diffusion du minaret-escalier et son lien avec les ibadites - Prevost, Virginie (Connected Stories: Contacts, Traditions and Transmissions in Premodern Mediterranean Islam, 2022)
Keywords: Archéologie -- Djerba

Les héritages de Méninx - Ben Omrane, Sadok (Mémoire plurielle de Djerba, 2014)
Keywords: Archéologie -- Djerba

Murex Shells as Raw Material : The Purple-Dye Industry and Its By-products : Interpreting the Archaeological Record - Alberti, Maria Emanuela (Kaskal, Rivista di storia, ambienti e culture del Vicino Oriente Antico, 2008)
Keywords: Archéologie -- Djerba; Murex -- Djerba

Meninx - geophysical prospection of a Roman town in Jerba, Tunisia - Lambers, Lena; Fassbinder, Jörg W. E.; Ritter, Stefan; Ben Tahar, Sami (Archaeopress, 2017)
Keywords: Antiquité; Archéologie -- Djerba

Recherches sur l'Africa Vetus, de la destruction de Carthage aux interventions césaro-augustéennes - Pasa, Béatrice (Université Toulouse le Mirail - Toulouse II, 2011)
L’Africa vetus, entre la destruction de Carthage et les interventions césaro-augustéennes, est traditionnellement perçue par l’historiographie comme une région dépourvue d’histoire, caractérisée par un paysage chaotique et dévasté. Pourtant, la reprise attentive de la documentation, principalement archéologique, permet de dresser un tout autre constat. Ainsi il apparaît que les conséquences du dernier conflit punico-romain n’ont pas entrainé l’annihilation de toute activité en Afrique nord-orientale. Les évolutions amorcées antérieurement à la chute de Carthage se prolongent, plus ou moins affectées par les bouleversements géopolitiques du milieu du IIe s. av. n. è. Dès lors, nous nous retrouvons face à une région en construction ou en reconstruction, qui connaît des changements, des bouleversements, parfois des reculs, mais reste toujours dynamique. Cette vie s’observe dans les différents domaines, au travers de l’étude de la population, de son identité et de son appréhension, de l’occupation et de la gestion du territoire, de la répartition des activités économiques et commerciales ainsi que de l’évolution des paysages cultuel et funéraire. À cette vision globale s’ajoute une approche régionale de ce territoire qui révèle, à l’intérieur d’un même ensemble, des constructions divergentes pour les quatre principales régions : la Zeugitane, le Byzacium, la région tellienne et la Petite Syrte. L’histoire de chacune est déterminée par son passé préromain, son action et son attitude durant la première moitié du IIe s. av. n. è. et au cours de la troisième guerre punique.
Keywords: Archéologie -- Djerba; Murex -- Djerba

Un curieux ensemble sculpté de l'Afrique romaine: les piliers de Meninx - Baratte, François; Ouertani, N. (Studi di archeologia in onore di Gustavo Traversari, 2004)
Keywords: Archéologie -- Djerba

Découverte épigraphique à Djerba (Tunisie): un complément à l'inscription CIL VIII, 22785 des Meningitani - Akkari-Weriemmi, Jenina (Lo spazio marittimo del Mediterraneo occidentale: geografia storica ed economia. Atti del XIV Convegno Internazionale di Studi, Sassari 7-10 dicembre 2000, 2002)
Keywords: Antiquité; Archéologie -- Djerba; Hâra, mosquée al- (Sedouikech, Djerba); Lucius Minicius Natalis

Aperçu succinct sur le fortin du site de Lalla Thala à Djerba (Tunisie) - Akkari-Weriemmi, Jenina (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2001)
Keywords: Antiquité; Archéologie -- Djerba

An island through time: Jerba studies - Fentress, Elizabeth; Drine, Ali; Holod, Renata; Aït Kaci, Ahmed (Journal of Roman Archeology. Supplements, 2009)
Keywords: Archéologie -- Djerba; Monuments -- Djerba; Sidi Garus, mosquée (Haddada, Djerba); Sidi Jmur, mosquée (El Groo, Djerba)

Shaking Up Architecture - Laurence, Lee Adair (Saudi Aramco World, 2001)
On Holod and Djerba
Keywords: Archéologie -- Djerba

La Produzione della ceramica a Pantelleria e la sua circolazione in età tardo antica - Baldassari, Roberta (Università degli studi di Sassari, 2014)
This research concerning the cooking pottery production in late roman time in the Island of Pantelleria, located in the Sicily Channel.This coarse ware consisted in pans, pots, casseroles and lids and large jars, useful to cook food and other raw materials as bitumen and pitch. This high refractoriness is given to the ceramic mixture by the vulcanic minerals peculiars form the clay of the island. The archaeological excavations conducted until now, discovered a large settlement in the Scauri Bay placed in the S-W coast of the island, datable from the second half of the IV to the end of the V century. The village based its economical activity on the cooking pottery production and its export, as evidenced by the shipwreck in the harbor of Scauri. The pottery materials found in the site and in the shipwreck, come from reliable contexts and it has been helpful to a thorough tipological and chronological study of this local ware production. The analysis of the attestations in the Central and Western Mediterranean, through the bibliography and some unpublished datas from Sicily, led to create some circulation maps across the centuries. This has allowed me to make some considerations and conclusions. It has been possible to realize a diachronic study, to distinguish forms and types from the III cent. B.C. to the V cent. A.D.. The pottery had a wide circulation in the Mediterranean, mostly from the second half of the IV to the beginning of the VI century.
Keywords: Archéologie -- Djerba

Qallāla fī ʿuṣūr al-qadīma al-majāl wa’l-insān - Ben Tahar, Sami (Al-thaqāfa al-amāzīghiyya : al-thawābit wa’l-mutaghayyirāt, 2018)
Keywords: Archéologie -- Djerba

جربة والتجارة المتوسطية في عهد البوني موقع غيزن مثلا - بن طاهر, سامي (الحياة الثقافية, 2013)
Keywords: Archéologie -- Djerba

الماء والمنشآت المائيّة بجزيرة جربة - باكير, خولة (كلية العلوم الانسانية والاجتماعية, 2014)
Keywords: Archéologie -- Djerba

5th-Century BC Himera and the Campanian Connection: Petrographic and Archaeological Studies on Western Greek Amphorae from Poseidonia and Elea Unearthed in the Necropolis of Himera - De Bonis, Alberto; Gassner, Verena; Ntaflos, Theodoros; Rizzo, Maria Luigia; Sauer, Roman; Serritella, Antonia; Vassallo, Stefano; Bechtold, Babette (Minerals, 2020)
Within the frame of an in-depth study of the corpus of about 560 western Greek transport amphorae (6th–5th century BC) yielded from excavations at the necropolis of the Dorian-Chalcidian colony of Himera in North-western Sicily, one of the most interesting issues consists in the determination of their provenance. Based on archaeological considerations, nearly 100 items have been attributed to southern Campania, specifically to Poseidonia and Elea. The present paper proposes a detailed combined archaeological-archaeometric investigation of 16 samples discovered at Himera and one at Jerba (Tunisia), of presumed Campanian provenance, compared with 4 local reference samples from Poseidonia and 6 samples of western Greek amphorae found at Pithekoussai and Elea, attributed to Poseidonia by previous archaeometric analysis. All samples have been submitted to a macroscopic fabric examination according to the standard methods of FACEM (Fabrics of the Central Mediterranean) and to petrographic investigation (polarised light microscopy) and digital image analyses of microstructures. Our study points to a Campanian provenance of the investigated amphorae and their distinction in a large group from Poseidonia and a small group from Elea. The identification of a numerous assemblage of 5th century BC Poseidonian transport vessels at Himera substantially underlines an earlier hypothesis about its ‘Campanian connection’ and allows for the reconstruction of an important Tyrrhenian commercial axis.
Keywords: Archéologie -- Djerba

Ghizène (Jerba) and Mediterranean trade from the 5th to the 3rd century BCE: The evidence of the Greek transport amphorae - Bechtold, Babette (Carthage Studies, 2019)
Keywords: Archéologie -- Djerba

Michèle Blanchard-Lemée (1936-2017) et l’Afrique antique - Darmon, Jean-Pierre (Antiquités africaines, 2019)
Keywords: Archéologie -- Djerba

Le Gargoulettes (orci perforati) per la pesca del polpo a Gerba (Tunisia) Iniziando una missione etnoarcheologica - Lugli, Francesca; Vidale, Massimo (Archeologia Postmedievale, 2000)
Keywords: Archéologie -- Djerba

Wool sheep and purple snails—Long‐term continuity of animal exploitation in ancient Meninx (Jerba/Tunisia) - Trixl, Simon; Ben Tahar, Sami; Ritter, Stefan; Peters, Joris (International Journal of Osteoarchaeology, 2020)
Keywords: Archéologie -- Djerba

Recherches sur la présence ottomane et espagnole sur l’île de Ğirba/Djerba à la lumière des témoignages archéologiques - Msellem, Zied (Faculté des Sciences Humaines et Sociales de Tunis, 2017)
L’objectif principal de cette étude tend à classer les différents témoignages d’occupation Espagnole et Ottomane sur l’île de Ğirba ainsi faire un recoupement des données historiques et archéologiques pour faire éclairer cette épisode de l'histoire de l’île
Keywords: Archéologie -- Djerba

Les vestiges archéologiques submergés ou en cours d’érosion sur les côtes sableuses de la Tunisie - Oueslati, Ameur (Revue tunisienne de géographie, 2002)
Keywords: Archéologie -- Djerba

15 ae 1998, 282: A Case Study of Public Benefaction and Local Politics - Liu, Jinyu (Ancient Documents and their Contexts, 2015)
Keywords: Archéologie -- Djerba; C. Serviulius Diodorus

Die gefährdete antike Stadt Meninx auf Djerba - Quist, Otto (archaeologieblog.de, 2016)
Keywords: Archéologie -- Djerba

Meninx: The Luxury of the Purple Dye Industry and the Richness of Architecture - Morton, Thomas ([Convegno Internazionale Dedicato al Tema "Le Ricchezze dell'Africa, Risorse, Produzioni, Scambi"], 2008)
Keywords: Archéologie -- Djerba

The Impact of Luxury: The Forum of Meninx, an architectural investigation - Morton, Thomas (University of Pennsylvania, 2003)
Keywords: Archéologie -- Djerba

Purple, marble, and barbarians: Meninx and the impact of luxury - Morton, Thomas (The 103rd Annual Meeting of the Archaeological Institute of America, 2002)
Keywords: Archéologie -- Djerba

Neues zur Stadtgeschichte von Meninx (Djerba). Die Ergebnisse der Grabungskampagne 2017 - Ritter, Stefan (Deutsches Archäologisches Institut, 2018)
Keywords: Archéologie -- Djerba

Arquitectura púnica: los monumentos funerarios - Prados Martínez, Fernando (Anejos de A EspA, 2008)
Keywords: Archéologie -- Djerba

Les Traces des installations laissées par l’occupation humaine, durant la Préhistoire, sur les Îles de Kerkennah, Djerba et la Presqu’Île de Zarzis - Hannachi, Khansa (Faculté des Sciences Humaines et Sociales, 2014)
Keywords: Archéologie -- Djerba

The Excavations of Count Byron Khun de Prorok in Carthage (1920-1925) III: Utica and Djerba - García Sánchez, Jorge (BSAA Arqueología, 2016)
Keywords: Archéologie -- Djerba

Preliminary remarks about the civil basilica at « Meninx » (Jerba, Tunisia) - Morton, Thomas (Carocci Editore, 2002)
Keywords: Antiquité; Archéologie -- Djerba

Constructed Landscapes: Designing Urban Centres in Roman Africa - Morton, Thomas (Beyond boundaries: connecting visual cultures in the provinces of ancient Rome, 2016)
Keywords: Archéologie -- Djerba

Le littoral de la Tunisie. Etude géoarchéologique et historique - Slim, Hédi; Trousset, Pol; Paskoff, Roland; Oueslati, Ameur (Centre national de la recherche scientifique, 2004)
Un programme de prospections extensives - à la fois archéologiques et géomorphologiques - a été réalisé le long des côtes de Tunisie de 1987 à 1997, depuis la frontière libyenne jusqu'à la frontière algérienne. Il était placé sous le double patronage de l'Institut National du Patrimoine de Tunis et de la Commission française de Coopération du Ministère des Affaires Étrangères. L'objectif poursuivi était double : du point de vue des géographes, mise en évidence des transformations de l'environnement littoral depuis l'antiquité, consécutives au relèvement du niveau marin et au déplacement de la ligne de rivage ; du point de vue des archéologues, reconnaissance et étude des vestiges d'installations antiques liées à la mise en valeur des ressources du littoral et de la mer, principalement les carrières de grès dunaire et surtout les activités halieutiques. C'était la première fois qu'une aussi longue section de l'espace côtier était placée ainsi sous les regards croisés de l'archéologie et de la morphologie. Une telle approche «géoarchéologique» bénéficie de la complémentarité des points de vue respectifs concernés. Pour la reconnaissance des paléoenvironnements récents, les géographes font de plus en plus appel aux «marqueurs» bien datés par les archéologues. En retour, la mise en évidence des modifications du littoral aide à considérer les données archéologiques et historiques dans un espace en réalité mutant. Dans la perspective du phénomène planétaire de montée des eaux lié au réchauffement actuel de l'atmosphère, ce type de recherche pourrait aider à formuler des indications utiles à la gestion des régions côtières.
Keywords: Archéologie -- Djerba

Témoignages archéologiques sur les activités halieutiques de Meninx - Drine, Ali (Ressources et activités maritimes des peuples de l'Antiquité: actes du colloque international de Boulogne-sur-Mer, 12, 13 et 14 mai 2005, 2008)
Keywords: Archéologie -- Djerba

La pourpre de « Meninx » - Drine, Ali (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2007)
Keywords: Archéologie -- Djerba

Le sanctuaire de Tala (île de Jerba) - Drine, Ali (Revue des études phéniciennes-puniques et des antiquités libyques, 2002)
Keywords: Archéologie -- Djerba

Les articulations de l’Afrique Mineure dans le Périple dit de Scylax - Cheyns, André; Isebaert, Labert; Mund-Dopchie, Monique; Desanges, Jehan (Heureux qui comme Ulysse: hommage à Monique Mund-Dopchie, 2013)
Les recherches scientifiques du Monique Mund-Dopchie, à qui ce volume rend hommage, s'articulent autour de trois axes essentiels : la survie des tragiques grecs à la Renaissance; la représentation, dans l'imaginaire antique, des régions situées aux confins du monde; la réception des récits de voyage grecs et latins à l'époque des Grandes Découvertes. C'est cette dernière orientation que les éditeurs ont privilégiée en organisant un colloque sur le "Voyage dans l'Antiquité grecque", afin d'illustrer quelques-uns des thèmes majeurs qui traversent l'oeuvre scientifique du Pr Monique Mund- Dopchie: la découverte de l'inconnu, l'attrait du lointain et la rencontre de l'Autre. La première partie de cette publication réunit quatre communications portant, d'abord sur le Voyage, et plus particulièrement sur les errances d'Ulysse
Keywords: Archéologie -- Djerba

Djerba, saint Hippolyte et le Stadiasme - Desanges, Jehan (Itinéraires de Saintes à Dougga. Mélanges offerts à Louis Maurin, 2003)
Keywords: Archéologie -- Djerba

Island Colonisation and Abandonment in Mediterranean Prehistory - Dawson, Helen Sarah (University College, 2005)
Keywords: Archéologie -- Djerba

Guarding a Well-Ordered Space on a Mediterranean Island - Holod, Renata; Kahlaoui, Tarek (The Archaeology of Medieval Islamic Frontiers, 2019)
For Ifriqiya, the Maghrib, and the eastern coast of al-Andalus, a ribāṭ can be defined as a coastal point of defense meant to host ghazīs, warriors for the faith or volunteers on the basis of religious commitment. From the eighth century onward, ribāṭs stretched along the seashore of Islamic Maghrib from Tripoli (Ṭarāblus) up to the east coast of al-Andalus. These were typically connected to another urban structure with an immediately supporting rural environment, or they could be isolated structures supplied from the sea. In one sense, they functioned in much the same way as stations along the ‘Abbasid-Byzantine land
Keywords: Archéologie -- Djerba; Hâra, mosquée al- (Sedouikech, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba)

Romanizing the Berbers - Fentress, Elizabeth (Past & Present, 2006)
Keywords: Archéologie -- Djerba

La ceramica tra l’età punica e la tarda antichità. Le anfore - Fontana, Sergio (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

An island in transition, Jerba between the fifth and the ninth centuries - Fentress, Elizabeth (Entre civitas y madīna: el mundo de las ciudades en la Península ibérica y en el Norte de África (siglos IV-IX), 2018)
Keywords: Archéologie -- Djerba; Monuments -- Djerba; Sidi Jmur, mosquée (El Groo, Djerba)

Peopling the Countryside: Roman Demography in the Albegna Valley and Jerba - Fentress, Elizabeth (Quantifying the Roman Economy: Methods and Problems, 2009)
The surveys of the Albegna Valley and the Island of Jerba were carried out respectively between 1979–1983 and 1995–2000 using similar methodologies (flow data and transect sampling). Each recovered over 1,000 sites, many of them Roman. They thus provide excellent comparable data for the study of ancient demographics. Using standard parameters, approximate densities per kilometre are calculated for each area, allowing the examination of change over time. The low figures for the Albegna Valley are then considered in the light of calculations regarding the population of Italy as a whole.
Keywords: Archéologie -- Djerba

Le produzioni ceramiche dell’isola di Gerba dall’età tardoantica alla prima età islamica: cambiamenti di modelli culturali e tecnologie - Cirelli, Enrico; Fontana, Sergio (Asociación Española de Arqueología Medieval, 2009)
Keywords: Archéologie -- Djerba

les ports phéniciens et puniques géomorphologie et infrastuctures - Carayon, Nicolas (Université Strasbourg II, 2008)
Keywords: Archéologie -- Djerba

Un «immondezzaio» di VI secolo da Meninx : la fine della produzione della porpora e la cultura materiale a Gerba nella prima età bizantina - Fontana, Sergio (Carocci Editore, 2000)
Keywords: Antiquité; Archéologie -- Djerba

The Jerba Survey : Settlement in Punic and Roman Periods - Fentress, Elizabeth (Carocci Editore, 2000)
Keywords: Antiquité; Archéologie -- Djerba

Ceramiche Almohadi e Hafsidi nell’isola di Jerba - Cirelli, Enrico (XXXV Convegno 2002: Ceramica in Blu. Diffusione e utilizzazione del blu nella ceramica, 2003)
Keywords: Archéologie -- Djerba

Towns and ports - Fentress, Elizabeth (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie -- Djerba

The towns and ports - Fentress, Elizabeth; Drine, Ali; Morton, Thomas; Ghalia, T. (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

The rural landscape and economy - Fentress, Elizabeth; Fontana, Sergio (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

The forts - Fentress, Elizabeth (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

Recherches sur le mausolée hellénistique d’Hinshīr Būrgū - Ferchiou, Naïdé (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

The Punic and Libyan Towns of Jerba - Fentress, Elizabeth (Phönizisches und punisches Städtewesen: Akten der internationalen Tagung in Rom vom 21. bis 23. Februar 2007, 2009)
Keywords: Archéologie -- Djerba

Tracing Urbanization in Early Modern Jerba - Kahlaoui, Tarek (The Mediterranean medina, 2009)
Keywords: Archéologie -- Djerba; Ghuraba, mosquée al- (Houmt Souk, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Monuments -- Djerba

Les fouilles de Meninx, résultats des campagnes de 1997 et 1998 - Drine, Ali (L’Africa Romana. Lo spazio marittimo del Mediterraneo occidentale: geografia storica ed economia. Atti del XIV Convegno Internazionale di Studi, Sassari 7-10 dicembre 2000, 2002)
Keywords: Antiquité; Archéologie -- Djerba

La circolazione di giare gerbine nel Mediterraneo occidentale: continuità e discontinuità nel commercio di derrate alimentari africane in età tardoromana e islamica - Cirelli, Enrico (Carocci Editore, 2002)
Keywords: Antiquité; Archéologie -- Djerba

Les ossements humains du site de Meninx - Roudesli, Sihem (Artisanat, métiers et savoir-faire dans le littoral tunisien, 2010)
Keywords: Archéologie -- Djerba

Water supply in the Roman period: aqueducts and cisterns - Wilson, Andrew (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

La ceramica a Jerba tra l’Età Punica e la Tarda Antichità - Capelli, C.; Ben Tahar, Sami; Fontana, Sergio (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

Les installations préhistoriques le long de la côte sud de la Tunisie - Boussoffara, Ridha (Artisanat, métiers et savoir-faire dans le littoral tunisien, 2010)
Keywords: Archéologie -- Djerba

De l’exploration archéologique de la Tunisie aux collections de mosaïques: le rôle des officiers français (1882-1891) - Blanchard-Lemée, Michèle (Carocci Editore, 2000)
Keywords: Antiquité; Archéologie -- Djerba

I Lotofagi nella tradizione antica: geografia e simmetria - Bianchetti, Serena (Carocci Editore, 2000)
Keywords: Antiquité; Archéologie -- Djerba

Dernière fouille : Relation entre Jerba et la Méditerranée - Ben Tahar, Sami (11ème Colloque Béchir Tellili Les activités maritimes à l’île de Jer-ba et en méditerranée durant les siècles, 2012)
Keywords: Archéologie -- Djerba

Hypothèses sur les techniques de pêche utilisées par les habitants du litoral nord-est de l'île de Djerba aux périodes punique et romaine, à partir des données archéologiques de Ghizène - Ben Tahar, Sami (Pêches méditerranéennes. Origines et mutations – Protohistoire-XXIe siècle, 2015)
Keywords: Archéologie -- Djerba

Henchir Taourit (Djerba), un site aux origines protohistoriques - Ben Tahar, Sami (Artisanat, métiers et savoir-faire dans le littoral tunisien, 2010)
Keywords: Archéologie -- Djerba

The punic and libyan cemeteries - Ben Tahar, Sami (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Antiquité; Archéologie -- Djerba

Nouvelle découverte dans la nécropole punique de Soûq el Guébli à Jerba - Ben Tahar, Sami (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2009)
Keywords: Antiquité; Archéologie -- Djerba

Les murex dans le Sud Est tunisien (Mahares, Zarzis et Jerba) - Ben Dhia, Wafa (Faculté des Sciences Humaines et Sociales, 2012)
Keywords: Archéologie -- Djerba; Murex -- Djerba

L’occupation du sol à Rhizène à l’époque antique. Les données de la prospection - Ben Tahar, Sami (Revue des études phéniciennes-puniques et des antiquités libyques, 2008)
Keywords: Archéologie -- Djerba

Henchir Bourgou (Jerba) à la lumière des nouvelles recherches archéologiques. - Ben Tahar, Sami (Mitteilungen des Deutschen Archäologischen Instituts, Römische Abteilung, 2018)
The site of Henchir Bourgou located on the northeast coast of Jerba was inhabited from Prehistory until Late Antiquity. It was probably the most important town and the capital of this island in Punic times. Its prosperity, for which there is evidence from imposing monuments such as the famous mausoleum and two Hellenistic temples recently uncovered, could be explained not only by its agricultural resources properly developed, but also from its flourishing maritime trade throughout the port of Ghizène. In Roman Imperial times, Henchir Bourgou became less important: the urban space had become smaller: gradually it had been replaced by another town set to be the capital of the Island for many centuries: Meninx.
Keywords: Archéologie -- Djerba

La pêche à Jerba à l'époque punique : l'apport de l'archéologie - Ben Tahar, Sami; Sternberg, Myriam (Rivista di Studi Fenici, 2011)
Keywords: Archéologie -- Djerba

Le site de Soûq el Guébli à l'époque punique : nouvelles recherches, nouvelles données - Ben Tahar, Sami (Institut national du patrimoine, 2010)
Keywords: Archéologie -- Djerba

Quelques réflexions sur les autochtones de Gigthis à l'époque punique. - Ben Tahar, Sami (Revue des études phéniciennes-puniques et des antiquités libyques, 2004)
Keywords: Archéologie -- Djerba

Ghizène (Jerba) and Mediterranean trade from the 6th to the 2nd century BCE - Ben Tahar, Sami (Carthage Studies, 2017)
Keywords: Archéologie -- Djerba

Henchir Bourgou (Djerba), Tunesien. Die Arbeiten der Jahre 2017 bis 2019 - Ben Tahar, Sami; Von Rummel, Philipp; Ritter, Stefan; Aoudi, Mekki; Dinies, Michèle; Fassbinder, Jörg W. E.; Mansel, Karin; Möller, Heike; Mukai, Tomoo; Peters, Joris; Reichmuth, Silvio; Trixl, Simon (e-Forschungsberichte des DAI, 2020)
The ancient site of Henchir Bourgou (Djerba), Tunisia, is the object of archaeological research conducted jointly by the Tunisian National Heritage Institute, the Ludwigs Maximilians University Munich and the German Archaeological Institute since 2017. The reports presents an overview on the activities in Henchir Bourgou done in 2017–2019 and gives an outlook on the potential of the site with its stratigraphy covering more than thousand years of settlement history.
Keywords: Archéologie -- Djerba

Henchir Tawrirt (Jerba) : un site libyque aux origines protohistoriques - Ben Tahar, Sami (Antiquités africaines, 2016)
Keywords: Archéologie -- Djerba

Le site antique de Guellala (Jerba). De la prospection à l’étude archéologique - Ben Tahar, Sami (Antiquités africaines, 2019)
Keywords: Archéologie -- Djerba

Une tombe monumentale d’époque républicaine à Marguène (île de Jerba, Tunisie) - Ben Tahar, Sami (Antiquités africaines, 2010)
Keywords: Archéologie -- Djerba

Le site punique de Ghizène (Jerba). Premiers résultats des fouilles 2008–2009. - Ben Tahar, Sami (Mitteilungen des Deutschen Archäologischen Instituts, Römische Abteilung, 2014)
The archaeological excavation conducted in Ghizène (northeast of the island of Jerba) between December 2008 and January 2009 unveiled a stratigraphy that runs, chronologically speaking, from the 6th century BC to the 1st century AD. In addition to the fishing resources concealed at the site, which can be inferred from the huts and various remains of fishermen discovered there, Ghizène seems to have been a Punic trading port – probably of Phoenician origin – very open to the Mediterranean trade. Thus we can explain the presence, in this island settlement, of ceramics imported from several sites around the Mediterranean, including Carthage, Athens, Corinth, Sicily, Southern Italy, Etruria, Malta, and even the Phoenician Levant
Keywords: Archéologie -- Djerba

A Fifth Century BCE Graffito from Ghizène (Jerba) - Schmitz, Philip; Docter, Roald F.; Ben Tahar, Sami (Orientalia, 2007)
Keywords: Antiquité; Archéologie -- Djerba

Landscape archaeology and urbanism at Meninx: results of geophysical prospection on Jerba (2015) - Ritter, Stefan; Ben Tahar, Sami; Fassbinder, Jörg W. E.; Lambers, Lena (Journal of Roman Archaeology, 2018)
This paper presents the results of the geophysical prospection conducted at the site of Meninx (Jerba) in 2015. This was the first step in a Tunisian-German project (a cooperation between the Institut National du Patrimoine, Tunis, and the Institut für Klassische Archäologie der Ludwig-Maximilans-Universität München), the aim of which is to shed light on the urban history of the most important city on the island of Jerba in antiquity. Meninx, situated on the SE shore of the island (fig. 1), was the largest city on Jerba during the Roman Empire and eponymous for the island's name in antiquity. The outstanding importance of this seaport derived from the fact that it was one of the main production centers of purple dye in the Mediterranean. With the earliest secure evidence dating to at least the Hellenistic period, Meninx saw a magnificent expansion in the 2nd and 3rd c. A.D. It was inhabited until the 7th c. when the city was finally abandoned.
Keywords: Antiquité; Archéologie -- Djerba

L’exploitation archéologique des vues satellitaires en Afrique du nord (Algérie, Tunisie) - Laporte, Jean-Pierre (Bulletin de la Société Nationale des Antiquaires de France, 2015)
Keywords: Antiquité; Archéologie -- Djerba

Islamic Pottery from Jerba (7th-10th century): Aspects of Continuity? - Cirelli, Enrico; Holod, Renata (La céramique maghrébine du haut Moyen Âge (VIII-X siècle): état des recherches, problemes et perspectives, 2011)
Keywords: Antiquité; Archéologie -- Djerba

La céramique maghrébine du haut Moyen Âge (VIIIe-Xe siècle): état des recherches, problèmes et perspectives - Cressier, Patrice; Fentress, Elizabeth (Collection de l'École française de Rome, 2011)
Keywords: Antiquité; Archéologie -- Djerba

Villas, wine and kilns: the landscape of Jerba in the late Hellenistic period - Fentress, Elizabeth (Journal of Roman Archaeology, 2001)
The island of Jerba emerges unobtrusively from its shallow waters. The landscape is flat, the vegetation varies from scrubland to sparse palms to large olive trees whose ample root-stocks suggest several centuries of life. The olive groves are ploughed to allow every possible drop of water to reach the roots. Dry farming of cereals is more or less pointless although, when rain is plentiful, barley will be thinly sown on land that is otherwise uncultivated. In this driest of Mediterranean zones, plentiful rain is barely more than the few showers which the 200-mm isohyet would suggest. In the interior of the island a few estates maintain irrigated cultivation, the luxuriant results of which recall Pliny's description of the oasis of Tacape; palms shelter fruit trees, which shelter pomegranates, which in turn shelter little vegetable plots. Wells provide water for these systems, the water trickling into the gardens through tiny channels (sāqiya). Today the water is pumped, but in the past each bucket had to be laboriously raised by mules or camels; their ramps form a distinctive component of the systems. High walls of mud (ṭābiya) enclose the irrigated gardens. However, in spite of the technological improvements, these gardens are less plentiful than in the past and, as the water table falls, it is more common to find an abandoned well than one in use.
Keywords: Antiquité; Archéologie -- Djerba

Les entrepôts de Méninx - Drine, Ali (Antiquités africaines, 2007)
Keywords: Antiquité; Archéologie -- Djerba

Peintures romaines de Tunisie - Barbet, Alix (Picard, 2013)
Ce livre, fruit d'un long et patient travail de recherche, rassemble les vestiges des décors d'une vingtaine de sites majeurs de Tunisie. Il nous révèle des peintures de grande qualité et d'une grande variété revêtant aussi bien les murs et plafonds des maisons ou des villas particulières que les thermes publics, les temples, les lieux de spectacles et les nécropoles. Les clichés sont présentés à côté de dessins de restitutions et les rapprochements avec des ensembles plus complets de l'Empire romain revèlent des thèmes tout à fait exceptionnels.
Keywords: Antiquité; Archéologie -- Djerba

Les routes de la navigation antique : Itinéraires en Méditerranée - Arnaud, Pascal (Collection des Hespérides, 2005)
La Méditerranée a été le trait d'union de la civilisation antique. Par elle ont transité les produits, les hommes, les idées, les modèles économiques, sociaux et politiques. Mais la mer n'est pas un milieu simple. Elle change avec les saisons, avec les aléas climatiques, et avec les savoirs des hommes, qui la rendent alternativement repoussante ou attirante, en font une auxiliaire ou une ennemie, une porte ouverte ou une barrière. Les routes, qui n'y sont ni tracées, ni balisées, sont le produit d'une alchimie complexe où se mêlent conditions naturelles, technologie, savoirs empiriques et règles commerciales. Déterminer les itinéraires précis qu'empruntaient les navigateurs, leurs variations saisonnières, et les temps nécessaires à leurs parcours, sont le fruit de la géographie historique. Ces rythmes du commerce, qui ont constitué la trame de l'économie méditerranéenne antique, ont fondé la représentation du monde des Anciens. Un voyage à travers l'espace-temps de la navigation antique donne les mesures de la mer transmises aux géographes anciens par l'expérience des marins
Keywords: Antiquité; Archéologie -- Djerba

La statue de Tmesset (Guellala-Djerba): La représentation d’un poète ou celle d’un dignitaire ? - Akkari-Weriemmi, Jenina (Mobilità delle persone e dei popoli, dinamiche migratorie, emigrazioni ed immigrazioni nelle province occidentali dell'impero romano"., 2006)
Keywords: Antiquité; Archéologie -- Djerba

Le columbarium de Dar Al Ghoula à Djerba (Tunisie) - Akkari-Weriemmi, Jenina (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2004)
Keywords: Antiquité; Archéologie -- Djerba

Le paysage funéraire libyco-punique de l’île de Djerba : Les caveaux de Mellita - Akkari-Weriemmi, Jenina (Revue des études phéniciennes-puniques et des antiquités libyques, 2004)
Keywords: Antiquité; Archéologie -- Djerba

Sépultures monumentales d’époque romaine à Djerba (Tunisie): Le mausolée temple de Henchir Ghardaïa - Akkari-Weriemmi, Jenina (Africa : Revue des Études et Recherches préhistoriques, antiques, islamiques et ethnographiques, 2003)
Keywords: Antiquité; Archéologie -- Djerba

The excavations at Meninx-Tala - Aït Kaci, Ahmed (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie -- Djerba

The sacred landscape - Aït Kaci, Ahmed (An Island Through Time: Jerba Studies : The Punic And Roman Periods, 2009)
Keywords: Archéologie -- Djerba

Meninx-Girba Nelle Fonti Letterarie Ed Epigrafiche - Agus, Annarita; Zucca, Raimondo (Carocci Editore, 2002)
Keywords: Archéologie -- Djerba